Examining Intersectoral Action as an Approach to Implementing Multistakeholder Collaborations to Achieve the Sustainable Development Goals - Joslyn Trowbridge; Julia Y. Tan; Sameera Hussain; Ahmed Esawi Babiker Osman; Erica Di Ruggiero (International Journal of Public Health, 2022)
Objectives: The Sustainable Development Goals (SDGs) re-orient action towards improving the social and ecological determinants of health and equity. SDG 17 calls for enhanced policy and institutional coherence and strong multi-stakeholder partnerships. Intersectoral action (IA) has a promising history in public health, including health promotion and global health. Some experts see IA as crucial to the SDGs. Yet less is known about how IA is conceptualized and what promising models exist with relevance to the SDGs. We sought to investigate how IA is understood conceptually and empirically.Methods: We conducted a narrative review of global public health and political science literatures and grey literature on the SDGs to identify theoretical models, case studies and reviews of IA research.Results: Multiple competing conceptualizations of IA exist. Research has focused on case studies in high-income countries. More conceptual clarity, analyses of applications in LMICs, and explorations of political and institutional factors affecting IA are needed, as is attention to power dynamics between sectors.Conclusion: IA is required to collaborate on the SDGs and address equity. New models for successful implementation merit exploration.